The Effect of Product Placement and Brand Awareness on Purchase Intention With Brand Image As a Moderating Variable: Kopiko Candy Among Korean Drama Viewers in Malang City - Willma Petir Nuraulia; Nur Asnawi (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze the influence of product placement and brand awareness on purchase intention, with brand image as a moderating variable among Korean drama viewers in Malang City. This study uses a quantitative approach with an associative research type. The sampling technique used purposive sampling with a total of 140 respondents who have watched Korean dramas and seen Kopiko products in Korean dramas. Data collection was conducted through an online questionnaire using a five-point Likert scale, while data analysis used the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS) with the help of SmartPLS. The results show that product placement and brand awareness have a positive and significant effect on purchase intention. In addition, brand image is able to moderate the relationship between product placement and purchase intention, but is unable to moderate the relationship between brand awareness and purchase intention. The results of this study indicate that Kopiko product placement in Korean dramas and high brand awareness can increase consumer purchasing interest. This study is expected to be a reference for companies in developing marketing strategies through entertainment media and building a positive brand image to increase consumer purchase intention.